2017
DOI: 10.1172/jci87406
|View full text |Cite
|
Sign up to set email alerts
|

Epiregulin and EGFR interactions are involved in pain processing

Abstract: that involves TRPV1, the PI3K/AKT/mTOR/4E-BP1 signaling pathway, and MMP-9, a molecule known to be involved in inflammation and the early stages of chronic pain (18).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(132 citation statements)
references
References 52 publications
9
118
1
Order By: Relevance
“…An intriguing theme emerging from these distinct interactomes is the prominence of epidermal growth factor receptor (EGFR) ligands as possible mediators of interactions between diseased tissue and mouse and human nociceptors. This finding is consistent with recent preclinical and clinical findings suggesting efficacy of blocking EGFR signaling for chronic pain (Kersten et al, 2013;Kersten et al, 2015;Martin et al, 2017;Kersten et al, 2019).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…An intriguing theme emerging from these distinct interactomes is the prominence of epidermal growth factor receptor (EGFR) ligands as possible mediators of interactions between diseased tissue and mouse and human nociceptors. This finding is consistent with recent preclinical and clinical findings suggesting efficacy of blocking EGFR signaling for chronic pain (Kersten et al, 2013;Kersten et al, 2015;Martin et al, 2017;Kersten et al, 2019).…”
Section: Introductionsupporting
confidence: 92%
“…Previous studies have implicated the EGFR pathway with chronic pain. Genetic associations studies link the EGFR and the EGFR ligand EREG chronic temporomandibular joint pain (Martin et al, 2017). Animal pain models suggest that EGFR activation by epiregulin encoded by the EREG gene promotes inflammatory and neuropathic pain and that EGFR signaling is critical for pain promoting effects of opioids (Martin et al, 2017;Puig et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is clear evidence that NGF and IL-6, among other pain-promoting molecules, can activate signaling pathways upstream of translation, a new mechanism by which mTORC1 is stimulated in nociceptors in acute and chronic pain conditions has been recently suggested: the EGFR [8]. This transmembrane receptor from the tyrosine kinase family is activated in neuropathic and chronic inflammation pain models.…”
Section: Eif4e Integrates Inputs From the Mapk And Mtor Pathways To Mmentioning
confidence: 99%
“…The potential role of EGFR gene polymorphism in humans has been assessed in several cohorts of patients with temporomandibular disorder (TMD), where a correlation between single nucleotide polymorphisms (SNPs) in EGFR and the incidence of TMD has been identified. Finally, studies in both humans and mice demonstrated that expression levels of epiregulin (EREG), an endogenous agonist of EGFR, are significantly increased in persistent pain conditions [8] and several clinical case reports suggest a role of EGFR in cancer pain [56,57]. Therefore, these studies collectively support a model wherein elevated levels of EREG lead to the stimulation of EGFR and its major downstream effector, mTORC1, to promote the translation of MMP9 and potentially other mRNAs that are involved in promoting pain hypersensitivity.…”
Section: Eif4e Integrates Inputs From the Mapk And Mtor Pathways To Mmentioning
confidence: 99%